Karakteristik plankton pada ekosistem terumbu karang alami dan terumbu buatan di Desa Tihik-Tihik Kota Bontang: Characteristics of plankton in natural coral reef ecosystems and artificial reefs in Tihik-Tihik Village, Bontang City - Wahyudi Maherezky; Ristiana Eryati; Abdunnur (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2023)
Coral reefs found in Tihik-Tihik village shows moderate coral reef status with indications of greater potential for damage so that protection efforts are needed. This research aims to analyze the abundance and community structure of plankton in reef ecosystems natural and artificial reefs. Sampling was carried out in the month of October – November 2020 at four stations at high and low tide with using a plankton net, then identified in the Water Quality Laboratory FPIK Unmul. The identified plankton consisted of 7 classes, namely, Bacillariophyceae (21 species), Conjugatophyceae (3 species), Copepoda (8 species), Cyanophyceae (1 species), Dinophyceae (10 species), Oligotrichea (3 species), Trebouxiophyceae (1 species). The highest total abundance of artificial reef ecosystems was at station 2 pairs with a total of 6741 ind/l. The diversity index (H') ranged from 2.12 to 2.22. The uniformity index (E) ranged from 0.92 – 0.96. The dominance index (D) ranges from 0.11 to 0.13. Sorenssen similarity index ranged from 29 – 68%.